2004
DOI: 10.1038/nm1045
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocal CD40 signals through p38MAPK and ERK-1/2 induce counteracting immune responses

Abstract: Macrophages play host to Leishmania major, a parasite that causes leishmaniasis in 500,000 people annually. Macrophage-expressed CD40, a costimulatory molecule, induces interleukin-12 (IL-12)-dependent and interferon-gamma (IFN-gamma)-dependent host-protective immune responses to Leishmania and other intracellular pathogens. Paradoxically, IL-10, another CD40-induced cytokine in macrophages, promotes Leishmania infection. How CD40 signaling regulates the secretion of these two counteractive cytokines remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
300
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(330 citation statements)
references
References 29 publications
26
300
2
2
Order By: Relevance
“…43 However, PSLinduced increase in IL-10 by LPS-stimulated macrophages may depend on ERK activity, because ERK activity leads to IL-10 production. 47,48 Furthermore, PSLs inhibited the rapid activation of p38 MAPK and may result in the subsequent slow enhancement of ERK activity in LPS-stimulated macrophages, because p38 MAPK and ERK cross-regulate each other such as the inhibition of one enhances the activation of the other. 47,49 Moreover, PSLs regulated the expression levels of IL-10 and IL-1b in the PB monocytes, the source of macrophage infiltrated in the ankle joints, and regulated the phosphorylation of p38, ERK and IkBa in the infiltrated macrophages in the synovium of the ankle joints of AA rats.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, PSLinduced increase in IL-10 by LPS-stimulated macrophages may depend on ERK activity, because ERK activity leads to IL-10 production. 47,48 Furthermore, PSLs inhibited the rapid activation of p38 MAPK and may result in the subsequent slow enhancement of ERK activity in LPS-stimulated macrophages, because p38 MAPK and ERK cross-regulate each other such as the inhibition of one enhances the activation of the other. 47,49 Moreover, PSLs regulated the expression levels of IL-10 and IL-1b in the PB monocytes, the source of macrophage infiltrated in the ankle joints, and regulated the phosphorylation of p38, ERK and IkBa in the infiltrated macrophages in the synovium of the ankle joints of AA rats.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the role of IL-2 in experimental visceral leishmaniasis is concerned, during the early phase of infection, IL-2 induces both IFN-␥-and IL-10-secreting T cells, perhaps as a function of the available IL-2 concentration, but IL-10 suppresses the IL-12 production by the APCs by differential regulation of MAPKs (26), reduces IL-12R expression on T cells (B. Saha, unpublished observation), and impairs IFN-␥ responsiveness of macrophages, resulting in the suppression of IFN-␥-mediated amastigote elimination. Being residents of the IL-10-rich splenic microenvironment, these T cells do not proliferate and suppress the activation of the infiltrating naive T cells, a phenomenon reminiscent of infectious tolerance (27).…”
Section: Discussionmentioning
confidence: 99%
“…Being residents of the IL-10-rich splenic microenvironment, these T cells do not proliferate and suppress the activation of the infiltrating naive T cells, a phenomenon reminiscent of infectious tolerance (27). Thus, Leishmania exaggerates and exploits the host's IL-10-dependent autoregulatory or a feedback servo-mechanism that prevents excessive inflammation-mediated host-tissue pathology, but supports unhindered parasite growth (25,26). Such a mechanism may operate in those viral infections in which the viral IL-10 (28, 29) may skew the immune response in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…FCM and RT-PCR detected the upregulated expression of CD40L after EBV infection. Other researchers reported that LMP1 plays a key role in B-cell transformation by EBV [15,16]. Although LMP1 is very similar to CD40 in terms of the signal transduction pathway and in the recruitment of TNF receptor-associated factor signaling molecules, it cannot entirely replace CD40 [17] because LMP1 and CD40 differ in some aspects.…”
Section: Figurementioning
confidence: 99%